Delayed Cardiac Metastasis from Renal Cell Carcinoma Caused by VHL Mutation (Journal of Kidney Cancer, 2023)
Cardiac metastasis caused by renal cell carcinoma (RCC) without vena caval involvement is rare. No mutation has been associated with this unique phenotype. A 77-year-old male presented to our clinic with a symptomatic right ventricular mass after nephrectomy for clear cell RCC (ccRCC). The mass was resected, and metastatic disease was confirmed. Targeted exon sequencing identified a VHL mutation (c.494T > G, p.V165G) in the resected specimen. While more than half of ccRCC cases are associated with VHL mutations, this case is the first to show the association between delayed, isolated cardiac metastasis and VHL V165G mutation. The phenotype presented 12 years after nephrectomy and localized to the right ventricular apex. Further genomic characterization of cases with cardiac metastases may provide clues regarding unique mutations noted. Patients exhibiting delayed spread of RCC to the heart must be screened for this mutation.